Raman scattering reveals strong LO-phonon-hole-plasmon coupling in nominally undoped GaAsBi: optical determination of carrier concentration - Steele, J.A.; Lewis, R.A.; Henini, M.; Lemine, O.M.; Fan, D; Mazur, Y.I.; Dorogan, V.G.; Grant, P.C.; Yu, S.Q.; Salamo, G.J. (Optical Society of America, 2014)
We report room-temperature Raman scattering studies of nominally undoped (100) GaAs1−xBix epitaxial layers exhibiting Biinduced (p-type) longitudinal-optical-plasmon coupled (LOPC) modes for 0.018≤x≤0.048. Redshifts in the GaAs-like optical modes due to alloying are evaluated and are paralleled by strong damping of the LOPC. The relative integrated Raman intensities of LO(Γ) and LOPC ALO/ALOPC are characteristic of heavily doped p-GaAs, with a remarkable near total screening of the LO(Γ) phonon (ALO/ALOPC →0) for larger Bi concentrations. A method of spectral analysis is set out which yields estimates of hole concentrations in excess of 5 × 1017 cm−3 and correlates with the Bi molar fraction. These findings are in general agreement with recent electrical transport measurements performed on the alloy, and while the absolute size of the hole concentrations differ, likely origins for the discrepancy are discussed. We conclude that the damped LO-phonon-hole-plasmon coupling phenomena plays a dominant role in Raman scattering from unpassivated nominally undoped GaAsBi.